“The role of parametric approach in design highest climatic performance buildings: local housing design patterns as a sample” (Journal of Planner and Development, 2020)
In light of increasing demand for energy consumption due to life complexity and its requirements, which reflected on architecture in type and size, Environmental challenges have emerged in the need to reduce emissions and power consumption within the construction sector. Which urged designers to improve the environmental performance of buildings by adopting new design approaches, Invest digital technology to facilitate design decision-making, in short time, effort and cost. Which doesn’t stop at the limits of acceptable efficiency, but extends to the level of (the highest performance), which doesn’t provide by traditional approaches that adopted by researchers and local institutions in their studies and architectural practices, limits to assumption of prototypes and their design characteristics to evaluate and select the efficient ones. Without comprehensive coverage to variables range and design possibilities with points of balance between the conflicting influence on performance. Forcing them to shorten, round up and exclude many (values and determinants) to avoid consequent of extra time and effort and the additional costs for performance assessment methods. All due to the cognitive weakness in adopt modern approaches, which become easier for designers to learning and apply. Highlighting (Performance-Based Parametric Design), which achieves this level of performance and avoided all the negative aspects of traditional approaches. Although this approach has been applied in several architecture trends, however, this research will focus on (climate performance and energy consumption). Highlighting a research problem, “lack of cognitive clearness about the nature of adopting parametric approach for performance-based design in order to achieve more efficient designs”. The research will focus on local housing patterns as a simplified model for applying the parametric approach, So the research goal will be “Highlighting and unveiling the nature of the parametric approach and its mechanism in performance-Based Design, to create and optimize design characteristics, towards most efficient designs within the local housing styles”. To achieve this goal was to build a hypothesis “The mechanism of parametric approach Managed to address a conflict influence of design characteristics in building’s thermal and light performance, such as (dimensions, locations orientation of building spaces and windows to wall area ratio). To reach a balancing point between them, for maximum reduction in cooling energy consumption in the summer, while keeping a comfortable level of natural lighting.” The research adopted an applied method to Revealed the parametric design mechanism To represent these characteristics as (parameters) to process and test them within three sequential process, (modeling, simulation and optimization), combined in one digital tool, uses algorithm to select the effective characteristics, that matching the resulted performance with specific criteria determined by the designer. The approach optimizes characteristics of three local housing pattern (Detached, Attached, and courtyard), within local environment, in order to achieve optimal efficient design. Ending with a set of conclusions about the importance and necessity of adopting this new approach within local architectural and environmental practices and studies.